Perbandingan Efektivitas Media Permainan Monopoli Kesehatan Gigi dan Video Edukasi Terhadap Pengetahuan Kesehatan Gigi dan Mulut - Melandani, Annisa P.; Parengkuan, Wulan G.; Wahyuni, Rizka (Universitas Sam Ratulangi, 2026)
Abstract: Oral and dental health issues remain a significant concern in Indonesia, particularly among school-aged children. One preventive effort that can be implemented is through engaging dental health education tailored to children's developmental stages. This study aimed to compare the effectiveness of the Monopoli Kesehatan Gigi (MOKEGI) board game and educational videos in improving oral health knowledge. The study was conducted among 4th to 6th-grade students at SD Negeri Munte, involving stages of socialization, pretest, educational intervention using MOKEGI and educational videos, followed by a posttest. The results showed that both media effectively increased students' oral health knowledge; however, the MOKEGI board game proved to be more effective. The Mann–Whitney test indicated a significant difference in posttest scores (p=0.023), with a higher mean rank in the MOKEGI group (28.94) compared to the video group (20.06). No significant difference was found in the pretest scores (p 0.473), indicating that the improvement was due to the educational media intervention. In conclusion, both education media are effective in improving sudents’ knowledge, however, MOKEGI is more effective than educational videos. Keywords: oral and dental health; elementary school children; educational game; educational video Abstrak: Masalah kesehatan gigi dan mulut masih menjadi tantangan serius di Indonesia, terutama pada anak usia sekolah. Salah satu upaya preventif yang dapat dilakukan adalah melalui pendidikan kesehatan gigi yang menarik dan sesuai dengan tahapan perkembangan anak. Penelitian ini bertujuan untuk membandingkan efektivitas media permainan Monopoli Kesehatan Gigi (MOKEGI) dan video edukasi terhadap peningkatan pengetahuan kesehatan gigi dan mulut. Penelitian dilaksanakan pada siswa kelas 4-6 di SD Negeri Munte dengan prosedur berupa sosialisasi, pemberian pretest, pelaksanaan intervensi menggunakan media MOKEGI dan video edukasi, serta posttest. Uji Mann–Whitney menunjukkan nilai signifikansi 0,023 pada posttest, dengan rerata rank kelompok MOKEGI sebesar 28,94 dan kelompok video edukasi sebesar 20,06. Tidak terdapat perbedaan bermakna pada hasil pretest (p=0,473), yang mengindikasikan bahwa peningkatan pengetahuan berasal dari intervensi media edukasi yang diberikan. Simpulan penelitian ini ialah kedua media efektif meningkatkan pengetahuan peserta didik, namun permainan MOKEGI terbukti lebih efektif. Kata kunci: kesehatan gigi dan mulut; anak sekolah dasar; permainan edukatif; video edukasi